Nanotechnology in combating biofilm: A smart and promising therapeutic strategy - Mohanta, Yugal Kishore; Chakrabartty, Ishani; Mishra, Awdhesh Kumar; Chopra, Hitesh; Mahanta, Saurov; Avula, Satya Kumar; Patowary, Kaustuvmani; Ahmed, Ramzan; Mishra, Bibhudutta; Mohanta, Tapan Kumar; Saravanan, Muthupandian; Sharma, Nanaocha (Frontiers in Microbiology, 2023)
It has been known since the beginning of civilization that infectious microorganisms produce deadly diseases in people, some of which can be fatal. The ability of microbes to create biofilms is a prominent pathogenic trait. It has a direct link to the emergence of persistent infections with enhanced disease severity. Resistance to the medications currently used in clinical practice is a challenge in removing such complex structures (biofilms). Hence it is crucial to look for novel substances with anti-biofilm action. It has recently become apparent that nanotechnology can be used to combat bacterial biofilm-related infections. Research into the effectiveness of nanoparticles (NPs) in the fight against bacterial infections is picking up speed. On the other hand, antimicrobial NPs continue to be the focus of most studies, with only a few clinical trials and a small number of in vitro results. In this scenario, nanotechnology offers safe delivery platforms for specific medicine delivery to treat various microbial illnesses brought on by biofilms. One of the plethoras of nanotechnology applications in drug delivery is the enhancement of the bioactive potential of pharmaceuticals. The current study describes the utilization of significant nanoparticles, including metal and metal oxide nanoparticles, liposomes, micro/nanoemulsions, solid lipid nanoparticles, and polymeric nanoparticles in the targeted drug delivery method used to manage microbial biofilms. Using these nanosystems has improved our knowledge regarding their contribution to fighting against biofilms.